2015
DOI: 10.1186/s12887-015-0492-7
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial of an intervention for infants’ behavioral sleep problems

Abstract: BackgroundInfant behavioral sleep problems are common, with potential negative consequences. We conducted a randomized controlled trial to assess effects of a sleep intervention comprising a two-hour group teaching session and four support calls over 2 weeks. Our primary outcomes were reduced numbers of nightly wakes or parent report of sleep problem severity. Secondary outcomes included improvement in parental depression, fatigue, sleep, and parent cognitions about infant sleep.MethodsTwo hundred thirty five … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
73
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(82 citation statements)
references
References 41 publications
3
73
0
6
Order By: Relevance
“…3,39 Parental mental health is also adversely affected among infants who have difficult bedtimes or do not sleep well. 7,8 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,39 Parental mental health is also adversely affected among infants who have difficult bedtimes or do not sleep well. 7,8 …”
Section: Discussionmentioning
confidence: 99%
“…36 Furthermore, infant sleep-related behaviors are associated with maternal sensitivity, relationship quality, parental emotional health, and parenting practices. 7, 8 Inadequate sleep has also emerged as an important risk factor for obesity 9, 10 with links between sleep and weight beginning in infancy. 1116 Short sleep duration during infancy is also associated with inadequate sleep later in childhood, 17 and therefore improving sleep-related behaviors and extending infant sleep duration has the potential to influence the long-term well-being of children and families.…”
mentioning
confidence: 99%
“…Infant sleep also affects parental sleep, which can affect other outcomes, including maternal sensitivity, relationship quality, parental emotional health, and parenting practices. 16,17 Fatigue is related to somatic complaints, anxiety, depression, paranoia, and crashes or unintentional injuries involving motor vehicles among healthy adults 39,40 and has been associated with postpartum depression, 41 abusive head trauma, and child abuse. 42 At a time when family-centered guidance is strongly encouraged, parent fatigue should be considered in any guideline related to infant sleep.…”
Section: Discussionmentioning
confidence: 99%
“…Another RCT in children (5–12 years) with ADHD who were randomized into two different groups (sleep hygiene practices and standardized behavioral strategies vs usual clinical care which routinely did not involve assessment and management of sleep problems) found that the active treatment group noted benefit in both sleep and behavioral issues, including ADHD symptoms [40]. Another sleep intervention study targeting infant offspring of parents with depression, found improvement in parental depression, limit setting, sleep quality, and fatigue [41]. Together, these studies provide a reasonable level of evidence that youth offspring of parents with Bipolar Disorder could benefit from sleep-related interventions.…”
Section: Resultsmentioning
confidence: 99%